“Análisis comparativo del controlador I-PD versus controladores clásicos” - Choto Reino, Anthony Israel (2024)
Within industrial processes, automation has gained crucial importance, driven by the need to optimize production through the use of advanced technologies. In this context, the classical PID controller has been widely adopted for its ability to enhance the response of industrial systems. However, despite its popularity and long-standing presence in the market, the traditional PID has certain disadvantages, such as generating overshoots and an aggressive response, which can be problematic in some processes. This research focuses on a comparative analysis between the classical PID controller and its I-PD variant, with a specific focus on temperature control through an embedded system, as well as in a flow process, where the variant stands out for its ability to handle process variations more effectively, demonstrating greater robustness against sudden changes and requiring less frequent adjustments. Through simulated and real tests using specialized software, it is shown that the I-PD variant outperforms the PID in several key aspects, offering smoother operation by reducing instabilities and overshoots of the process variable (PV) by 11.53% for temperature processes and 22.22% for flow processes, although its dead time increases by 66.6% compared to the PID in both cases. Despite this, the stabilization times in most processes are similar between both controllers.